Irrigated Corn Response to Long-Term Nitrogen and Phosphorus Fertilization - A. Schlegel; D. Bond (Kansas Agricultural Experiment Station Research Reports, 2021)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated corn in western Kansas. In 2020, N applied alone increased yields by 85 bu/a, whereas P applied alone increased yields 10 bu/a. Nitrogen and P applied together increased yields up to 136 bu/a which is 11 bu/a less than the 10-year average of 147 bu/a. The application of 120 lb N/a (with highest P rate) produced 98% of maximum yield in 2020, which is greater than the 10-year average (2011–2020). The application of 80 instead of 40 lb P2O5/a increased average yields 1 bu/a. The 10-year average grain N content reached a maximum of 0.6 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu). At the highest N and P rate, apparent fertilizer nitrogen recovery in the grain (AFNRg) was 43% and apparent fertilizer phosphorus recovery in the grain (AFPRg) was 63%. Nitrogen fertilization increased soil organic matter and decreased soil pH. Phosphorus fertilization at 40 lb/a P2O5was not sufficient to maintain soil test levels.
Keywords: nitrogen fertilization; phosphorus fertilization; irrigated corn; long-term fertility; nutrient removal